2020
DOI: 10.1089/dia.2019.0517
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Daily Physical Activity as Measured by Commonly Available Wearables on Mealtime Glucose Control in Type 1 Diabetes

Abstract: Objective: In contrast with exercise, or structured physical activity (PA), glycemic disturbances due to daily unstructured PA in patients with type 1 diabetes (T1D) is largely underresearched, with limited information on treatment recommendations. We present results from retrospective analysis of data collected under patients' free-living conditions that illuminate the association between PA, as measured by an off-the-shelf activity tracker, and postprandial blood glucose control. Research Design and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…It was able to detect COVID-19 in the pre-symptomatic period as well as the symptomatic phase of the patients, with a precision score of 0.91 (CI: 0.854–0.967) [ 10 ]. Cho et al proposed a one-class SVM method that can detect COVID-19 23.5–40% earlier compared to the method of Mishra et al [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was able to detect COVID-19 in the pre-symptomatic period as well as the symptomatic phase of the patients, with a precision score of 0.91 (CI: 0.854–0.967) [ 10 ]. Cho et al proposed a one-class SVM method that can detect COVID-19 23.5–40% earlier compared to the method of Mishra et al [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
“…Further, assessing PA quantitatively may show to be useful in making mealtime treatment decisions. It was also observed that participating in PA every day demonstrated an immediate or later impact on glucose control [ 30 ]. Akyol et al reported a novel consumer-wearable device called Diafit that works as a customizable glucose monitor for diabetes patients [ 40 ].…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
“…182 Commercially available wearable trackers have been utilized as surrogates for exercise in some AID devices with some success. 183 Extreme exercise or exercise with inadequate insulin levels can cause ketosis. 184 A continuous ketone sensor is being developed by PercuSense 185 with clinical studies likely beginning in 2021.…”
Section: The Dts Guideline For Continuous Glucose Monitors and Automated Insulin Dosing Systems In The Hospitalmentioning
confidence: 99%
“…Smartphone apps to log daily events 10 , 11 and calculate bolus insulin are increasingly being adopted to successfully reduce the daily burden associated with T1D self-management. Other wearables, such as wristbands, have been used in recent literature to estimate physical activity for T1D subjects 12 , 13 . Nonetheless, the clinical efficacy of apps and sensor wristbands remains unproven 14 , and there is a lack of an integrated platform that synchronizes the real-time physiological measurements of sensor wristbands and other wearable devices to improve decision support 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%